Growth and Yield of Kalimantan Landrace Rice and “IPB 8G” as Affected by Dose and Time of Application of Nitrogen Fertilizer - Faisal, Faisal; Lubis, Iskandar; Junaedi, Ahmad; Sugiyanta, Sugiyanta (Journal of Tropical Crop Science, 2019)
The study aimed to determine the effect of nitrogen fertilizer dose and the frequency of application on the growth and production of landrace rice Kalimantan and a new rice cultivar "IPB 8G". The study was conducted in December 2017 until June 2018 at the Sawah Baru Experimental Field, Bogor Agricultural University, West Java, Indonesia. The experimental design was a split-split plot consisting of three treatment factors, i.e. rice cultivars (main plots), fertilization time (sub-plots) and fertilizing doses (sub-plots). The three rice cultivars used in this trial were local cultivars "Mayas" and "Samarinda", and a newly developed rice cultivar "IPB 8G". The application rates of Nitrogen were 0, 75, and 150 kg N.ha-1 applied at different phases of rice growth: 50% N dose was applied at planting, 25% N dose at the vegetative phase, and 25% at the primordial phase. The different rates of N fertilizer were applied four times, 40% at planting, 20% during the vegetative phase, 20% at the primordial phase, and 20% at heading. Each treatment consisted of three replications totalling 54 experimental units. The N fertilizer application gave a significant effect on all growth parameters except for the harvest index. Time of fertilization significantly affected rice panicle number per hill and harvest index. There were significant differences in the growth of the three rice cultivars, except for the number of tillers. Rice crops fertilized three times with a dose of 75 kg N.ha-1 had the highest number of tillers at 5 week after planting, but it was not significantly different from N at 150 kg.ha-1. The highest grain yield of 2.9 t.ha-1 was obtained from "IPB 8G" cultivar fertilized with 75 kg.ha-1 of nitrogen.